Genomic epidemiology and antimicrobial resistance of Morganella clinical isolates between 2016 and 2023 - Zhu, Wentao; Liu, Qian; Liu, Jinlv; Wang, Yaqi; Shen, Hong; Wei, Ming; Pu, Ji; Gu, Li; Yang, Jing (Frontiers in Cellular and Infection Microbiology, 2025)
Morganella morganii is a Gram-negative, opportunistic pathogen that is often associated with nosocomial infections. Here, the genomic characteristics and antimicrobial resistance (AMR) of Morganella clinical isolates between 2016 and 2023 were determined. A total of 218 clinical isolates were mainly identified from urinary tract (48.2%) and respiratory tract (16.5%), with 105 isolates randomly selected for whole genome sequencing. The highest rates of antibiotic resistance were observed with SAM (68.3%), followed by CIP (39.9%), and SXT (37.2%). Distance analysis suggested that the 105 newly sequenced isolates could be divided into two groups: M. morganii subsp. morganii and M. morganii subsp. sibonii. While, the average nucleotide identity between these groups showed only 91.5-92.2% similarity, raising the possibility that they may be distinct species. Phylogenomic analysis revealed that the 102 M. morganii isolates fell into six clades, with clades 4-6 making up the majority. Core genome multi-locus sequence type analysis indicted high genomic diversity among different hosts and relatively stability (< 10 SNPs accumulated over three years) within the same host. Together with epidemiological data, isolates of four genetic clusters could be possible nosocomial transmissions. The identified 80 AMR genes belonged to 15 drug-related classes, with tet(B) gene being the most prevalent, followed by sul1, catA2, and sul2 genes. This study provided comprehensive genomic insights and AMR patterns of Morganella isolates in China, highlighting the necessity for continuous monitoring through whole genome sequencing.